Harms of exercise training in patients with cancer undergoing systemic treatment: a systematic review and meta-analysis of published and unpublished controlled trialsResearch in context - Simon N. Thomsen; Ian M. Lahart; Laura M. Thomsen; Martin K. Fridh; Anders Larsen; Morten Mau-Sørensen; Kate A. Bolam; Ciaran M. Fairman; Jesper F. Christensen; Casper Simonsen (EClinicalMedicine, 2023)
Summary: Background: Exercise is recommended for people with cancer. The aim of this study was to evaluate the harms of exercise in patients with cancer undergoing systemic treatment. Methods: This systematic review and meta-analysis included published and unpublished controlled trials comparing exercise interventions versus controls in adults with cancer scheduled to undergo systemic treatment. The primary outcomes were adverse events, health-care utilization, and treatment tolerability and response. Eleven electronic databases and trial registries were systematically searched with no date or language restrictions. The latest searches were performed on April 26, 2022. The risk of bias was judged using RoB2 and ROBINS-I, and the certainty of evidence for primary outcomes was assessed using GRADE. Data were statistically synthesised using pre-specified random-effect meta-analyses. The protocol for this study was registered in the PROESPERO database (ID: CRD42021266882). Findings: 129 controlled trials including 12,044 participants were eligible. Primary meta-analyses revealed evidence of a higher risk of some harms, including serious adverse events (risk ratio [95% CI]: 1.87 [1.47–2.39], I2 = 0%, n = 1722, k = 10), thromboses (risk ratio [95% CI]: 1.67 [1.11–2.51], I2 = 0%, n = 934, k = 6), and fractures (risk ratio [95% CI]: 3.07 [3.03–3.11], I2 = 0%, n = 203, k = 2) in intervention versus control. In contrast, we found evidence of a lower risk of fever (risk ratio [95% CI]: 0.69 [0.55–0.87], I2 = 0% n = 1109, k = 7) and a higher relative dose intensity of systemic treatment (difference in means [95% CI]: 1.50% [0.14–2.85], I2 = 0% n = 1110, k = 13) in intervention versus control. For all outcomes, we downgraded the certainty of evidence due to imprecision, risk of bias, and indirectness, resulting in very low certainty of evidence. Interpretation: The harms of exercise in patients with cancer undergoing systemic treatment are uncertain, and there is currently insufficient data on harms to make evidence-based risk-benefits assessments of the application of structured exercise in this population. Funding: There was no funding for this study.